Awareness and Ownership of Family Takaful Scheme Among Muslim Community in Malaysia - Abd Manab, N.; Ab. Rashid, R.; Ibrahim, Y. (Universiti Sains Islam Malaysia, 2024)
This study is an attempt to obtain a deeper understanding of the factors influencing the purchase of FTS. Specially, the study focus on the respondents' awarencss of the existence of the FTS, the respondents' knowledge and perception on certain characteristics and operations of the scheme, and other additional factors that might induce the respondents to purchase the scheme. Result of the study indicate that nearly 50 percent of the respondents are aware of the existence of FTS. However only 11.8 percent of those respondents actually own the policy. The low percentage might be due to the perception of those respondents who still have doubts whether the takaful operations are entirely free of riba. In general, the findings indicate that the respondents lack the proper understanding of certain characteristics and operations of FTS.